Management of Pediatric Mixed Phenotype Acute Leukemia in India - Shah Kajal; Panchal Harsha; Patel Apurva; Chinmay Doctor; Yadav Rajan (Achievements and Challenges of Medicine and Medical Science Vol. 10, 2025)
Background: Acute leukemia may be classified as myeloid, B, or T lymphoid in origin according to the antigenic profile of the blasts. Mixed-phenotype acute leukemia (MPAL) represents a rare heterogeneous group of acute leukemia in pediatric patients. MPAL has different clinicopathological and genetic character representatives, so diagnosis and treatment represent challenges. Management is more complex in low– middle-income countries (LMICs). Aim: The primary aim of this study is to describe the diagnosis and treatment outcomes of MPAL patients in a developing country. Methods: In the present study, eight pediatric patients newly diagnosed with MPAL from January 2005 until December 2015 were analyzed retrospectively. Cytogenetic analysis showed chromosome complements in all the metaphases from BM samples that follow the International System for Human Cytogenetic Nomenclature. Patients were treated with AML- or ALL-like induction therapy according to the BM aspirate immunophenotypic markers. Results: Three pediatric patients (37.5%) were diagnosed with T/Myeloid and Five (62.5%) with B/Myeloid through immunophenotyping of Eight MPAL patients. There were seven males as well as one female. The average age was 9 (range 4-13 years). Fever as well as lymphadenopathy were found in 6 (75%) as well as 4 (50%) of MPAL patients, respectively. We found KMT2A gene rearrangement in one patient, Philadelphia-positive chromosomes in one, and FMS-like tyrosine kinase three internal and duplication (FLT3-ITD) in two patients. Eight patients (100%) received acute lymphoblastic leukemia (ALL) induction; among them, six patients (75%) achieved complete remission (CR) with no induction deaths as well as two of the eight patients with induction failure were switched to AML therapy. Two patients (25%) started therapy with acute myeloid leukemia (AML) induction as well as both (100%) achieved CR and then received consolidation therapy after AML induction treatment. The 5-year event-free survival (EFS) and overall survival (OS) rates were 75% and 100%, while the cumulative incidence of relapse was found in one FLT3-ITD. B/myeloid, as well as one KMT2A, rearranged gene T/myeloid (25%) with a median follow-up duration of 8 years as well as treated with a hyper-CVAD regimen (combination of chemotherapy drugs including cyclophosphamide, vincristine), Adriamycin, as well as dexamethasone) induction, as well as achieved remission. Patients treated with ALL-directed therapy had a 5-year EFS rate of 67% and an OS rate of 100%. FLT3-ITD mutation showed a significantly lower 5-year EFS rate of 50%. 5-year EFS and the OS of MPAL patients were 60% and 100%, respectively. ALL induction treatments demonstrated higher remission rates in pediatric MPAL without mortality. Several studies have also investigated optimal upfront therapy for patients with MPAL, as well as support the notion that ALL treatment regimens tend to lead to better overall survival than AML-based regimens. Conclusion: ALL-directed therapy for pediatric MPAL is very effective. However, more recently, the treatment has changed due to improved diagnostic criteria, genomic techniques, and the observation that ALL-like regimens in pediatric and adult populations are associated with superior treatment response.